2015
DOI: 10.3389/fmicb.2015.01282
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Role for Bacterial Cellulose in Environmental Interactions: Lessons Learned from Diverse Biofilm-Producing Proteobacteria

Abstract: Bacterial cellulose (BC) serves as a molecular glue to facilitate intra- and inter-domain interactions in nature. Biosynthesis of BC-containing biofilms occurs in a variety of Proteobacteria that inhabit diverse ecological niches. The enzymatic and regulatory systems responsible for the polymerization, exportation, and regulation of BC are equally as diverse. Though the magnitude and environmental consequences of BC production are species-specific, the common role of BC-containing biofilms is to establish clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 354 publications
(415 reference statements)
1
69
0
Order By: Relevance
“…The study showed that the ability of mutants, i.e., Δ cytR , Δ fliC, flhD ::Tn5, and Δ motA to adhere themselves to plant tissues was significantly lower than the wild type ( Figure 7 ). It has been reported that cellulose synthesized by pathogens and symbionts is essential for host colonization and survival in stress conditions (Augimeri et al, 2015). We have previously reported that bacteria-associated with pellicle/AL biofilm except for aerobically grown logarithmic- and stationary-phase cells of the D. dadantii 3937 are more resistant to survival in acidic pH (4.0), oxidative stress and high osmolarity (Haque et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that the ability of mutants, i.e., Δ cytR , Δ fliC, flhD ::Tn5, and Δ motA to adhere themselves to plant tissues was significantly lower than the wild type ( Figure 7 ). It has been reported that cellulose synthesized by pathogens and symbionts is essential for host colonization and survival in stress conditions (Augimeri et al, 2015). We have previously reported that bacteria-associated with pellicle/AL biofilm except for aerobically grown logarithmic- and stationary-phase cells of the D. dadantii 3937 are more resistant to survival in acidic pH (4.0), oxidative stress and high osmolarity (Haque et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Pantoea ananatis can also promote plant growth through the production of cellulose (Megías et al ., 2016) and indole acetic acid (IAA) (Kim et al ., ; Megías et al ., 2016). The production of bacterial cellulose aids in inter‐domain attachments and biofilm formation, allowing growth‐promoting bacteria to effectively deliver growth‐promoting agents to their host plant (Augimeri et al ., ). IAA is a phytohormone that can have both beneficial and deleterious effects on the host plant (Spaepen et al ., ).…”
Section: Pantoea Ananatis In the Age Of Biotechnologymentioning
confidence: 97%
“…The ability of pathogenic bacteria to colonize a plant may also be influenced by their interactions with other microorganisms either positively or negatively (Deering et al, 2012). If other microorganisms supply carbon sources (via degradation of cell wall polymers or induced secretion of sugars), or sequester antimicrobials, this can enhance pathogen colonization (Bais et al, 2006;Warriner et al, 2009;Augimeri et al, 2015). Alternatively, plant pathogens that wound or destroy living tissue may create a microenvironment that is suitable for the survival and/replication of human pathogens (Rashid et al, 2016).…”
Section: Internalizationmentioning
confidence: 99%